Retrenchment, Reform, Continuity: Welfare under the Coalition. (February 2015) - Gaffney, Declan
Abstract : The Coalition's record on working age social security is reviewed under the headings of continuity (with the policies of the previous government), retrenchment and reform. Under continuity, the Coalition's decision to proceed with the previous government's planned reassessment of incapacity benefit claims was a notable policy mistake which led to the near-collapse of the assessment system by 2014. Retrenchment measures are dominated by benefit uprating changes which, along with measures targeting higher-income groups, have been less regressive than alternative approaches to expenditure reduction. However these changes were accompanied by a number of smaller-scale retrenchment measures, with substantial cumulative impacts on income. Retrenchment has thus been less regressive than it might have been but more regressive than it needed to be, taking the retrenchment targets as given. Policy failure and exogenous economic factors have offset the effect of retrenchment measures, with the result that expenditure by 2014/15 was little different to that planned in the Labour government's last budget. Full implementation of major reforms has been deferred to the next parliament. The main achieved policy change has been an unprecedented tightening of the benefit sanctions regime.